2012
DOI: 10.1063/1.4757659
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of laminar jet impingement and hydraulic jump on a horizontal surface with slip

Abstract: This paper explores the influence surface slip, uniform in all directions with constant slip length, exerts on the physics of laminar jet impingement on a flat horizontal surface. Slip exists on superhydrophobic surfaces, and due to the relatively thin film dynamics associated with the growth of the laminar jet after impingement, its influence on the fluid physics is significant. An analysis based on momentum considerations is presented that allows prediction of the relevant thin film parameters as a function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 36 publications
2
43
1
Order By: Relevance
“…Predicting the slip velocity requires estimation of the slip length at the surface, as discussed in Refs. [40,46]. A previous study by Joseph et al [68] suggested that the effective slip length [44], b ef f , is related to the lateral length scale between the surface structures, L, through b ef f = αL, where α 0.28 leads to the best fitting of the experimental results.…”
Section: Theoretical Formulationmentioning
confidence: 95%
See 1 more Smart Citation
“…Predicting the slip velocity requires estimation of the slip length at the surface, as discussed in Refs. [40,46]. A previous study by Joseph et al [68] suggested that the effective slip length [44], b ef f , is related to the lateral length scale between the surface structures, L, through b ef f = αL, where α 0.28 leads to the best fitting of the experimental results.…”
Section: Theoretical Formulationmentioning
confidence: 95%
“…In other words, barring the point of impingement, an air layer is trapped in the micro-and nanoscale cavities of the solid target, thus changing the hydrodynamic [44] and thermal [45] boundary conditions. Hydrodynamically, researchers have accounted for this by introducing an aggregate slip boundary condition [46][47][48][49] at the surface, thus accounting for the shear-free boundary condition over the cavities and the no-slip boundary condition on the structures. From a thermal point of view, for metallic substrates, the boundary condition at the liquid-gas interface can be considered adiabatic due to the low thermal conductivity of the gas, while a conventional convection boundary condition exists at the liquid-solid interface [50].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, much work has focused on drag reduction using SH surfaces in the turbulent flow regime [13][14][15][16]. Substantial work has also been performed regarding drops [17][18][19][20][21] as well as jet impingement on SH surfaces [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The coatings of the target plate using different sandpapers create superhydrophobic surfaces (Gogte et al 2005). Since superhydrophobic surfaces reduce the growth of the boundary layer and therefore reduce the shear stress and friction, it increases the radius of the hydraulic jump (Prince et al 2012). Figure 7 shows the effect of the target plate roughness on circular hydraulic jump radius at different flow rates.…”
Section: Fig 5 Effect Of the Flow Rate On The Downstream Fluid Deptmentioning
confidence: 99%
“…Since Onda et al (1996) first demonstrated artificial superhydrophobic surfaces in 1996, many studies have been reported on the production of superhydrophobic surfaces, their applications and properties (Shirtcliffe et al 2010;Ma and Hill 2006). Prince et al (2012) investigated the influence of superhydrophobic surfaces on the physics of laminar jet impingement on a flat horizontal surface. Their results indicated that the formation of hydraulic jumps on superhydrophobic surfaces, reduced the growth of the boundary layer, fluid height and friction coefficient, and thus increases the hydraulic jump radius.…”
Section: Introductionmentioning
confidence: 99%